2007
DOI: 10.1007/s00405-007-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study comparing postoperative pain between coblation and bipolar scissor tonsillectomy

Abstract: Coblation tonsillectomy has shown promising results with respect to postoperative pain when compared with other techniques. Our study was designed to compare this technique with bipolar scissor tonsillectomy. Forty adult patients with a history of chronic or recurrent tonsillitis referred for standard tonsillectomy were recruited and randomized into two groups. Twenty were operated with Coblator and 20 with bipolar scissors. Exclusion criteria were a history of quinsy, bleeding disorder, or any major health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…After the introduction of radiofrequency devices such as the Harmonic scalpel and Coblator, one report showed that the Coblator was superior to the Harmonic scalpel and electrocautery [3]. One study revealed that bipolar scissors were better than the Coblator in the aspect of pain [15]. Tonsillectomy using the Harmonic scalpel did not show consistent favorable results [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of radiofrequency devices such as the Harmonic scalpel and Coblator, one report showed that the Coblator was superior to the Harmonic scalpel and electrocautery [3]. One study revealed that bipolar scissors were better than the Coblator in the aspect of pain [15]. Tonsillectomy using the Harmonic scalpel did not show consistent favorable results [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Return to normal activity time is reported later by Hasan et al (9) and earlier by Di Rienzo et al (8) in the PKT group. In Figure 1.…”
Section: Discussionmentioning
confidence: 59%
“…Di Rienzo et al (8) reported less intraoperative blood loss in the PKT group where as Hasan et al (9) found more blood loss in the PKT group. In our study we observed less intraoperative blood loss in the PKT group.…”
Section: Discussionmentioning
confidence: 96%
“…As has been found by the technique pioneers, Timms and Temple, as well as by Hasan et al and Roje et al, children and adults who were operated on by coblation suff ered statistically signifi cantly less postoperative pain and experienced a considerably faster return to normal dietary habits [68, 15,22]. Stoker et al have demonstrated that radiofrequency tonsillectomy is superior to diathermy in terms of reduced postoperative pain, local edema, and faster wound healing [11].…”
Section: Discussionmentioning
confidence: 99%